2017
DOI: 10.15537/smj.2017.12.20926
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference as a marker of obesity and a predictor of cardiometabolic risk among Saudi subjects

Abstract: Objectives:To determine the optimal cutoff value for neck circumference (NC) that define overweight/obesity and assess its predictive potential for cardiometabolic risks (CMR) among Saudi subjects.Methods:A cross sectional study of 785 adults recruited from a public health awareness campaign in Medina, Saudi Arabia during June 2015. Waist circumference (WC), NC, body mass index (BMI), blood pressure (BP), and random blood glucose (RBG) were assessed, and the presence of CMR were collected by a questionnaire. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 12 publications
4
21
2
Order By: Relevance
“…Recently, there is a growing interest in the utility of neck circumference (NC) in identifying people with obesity. This new index of upper body adiposity is easy to determine, does not require much body exposure, and was found to correlate with other obesity indices and body fat [10][11][12][13][14]. In the Framingham Heart Study, NC was found to be positively associated with BMI, visceral adipose tissue (VAT) and other cardiovascular disease risk factors [10].…”
Section: Introductionmentioning
confidence: 96%
“…Recently, there is a growing interest in the utility of neck circumference (NC) in identifying people with obesity. This new index of upper body adiposity is easy to determine, does not require much body exposure, and was found to correlate with other obesity indices and body fat [10][11][12][13][14]. In the Framingham Heart Study, NC was found to be positively associated with BMI, visceral adipose tissue (VAT) and other cardiovascular disease risk factors [10].…”
Section: Introductionmentioning
confidence: 96%
“…(CC with BMI 0.5, with WC 0.7 in male and 0.5 in female. 8 ) These cutoff levels for NC were associated with a significantly increased risk for diabetes, dyslipidemia, and hypertension. 8 Significant positive correlation with BMI and WC were also reported in young adults from Bosnia and India.…”
Section: Discussionmentioning
confidence: 89%
“…8 ) These cutoff levels for NC were associated with a significantly increased risk for diabetes, dyslipidemia, and hypertension. 8 Significant positive correlation with BMI and WC were also reported in young adults from Bosnia and India. 9,10 (with BMI r 0.70, 0.53, with WC 0.48, 0.38 in males and females 9 , r with BMI 0.81 10 ) In Bosnian adults, Cut off value of NC was 36cm, 38 cm, 30.9 cms and 33 cms in males and females respectively for overweight and obesity.…”
Section: Discussionmentioning
confidence: 89%
“…All studies were used cross-sectional data and had medium to high-quality. These studies were published between the year 2003 and 2017 and performed in the United states [21,25,48,51,55], China [19,20,23,28,29,53,56,57], India [27], Israel [38,39], Turkey [31,34,52], Korea [42], Japan [44], Iran [54], Spain [26], Bulgaria [50], Portugal [43], Brazil [30,40,47] and Saudi Arabia [49]. The results of most studies revealed that there is positive correlation between NC and blood pressure.…”
Section: Resultsmentioning
confidence: 99%
“…NC is an important and novel anthropometric index and has multiple advantages than previous indices like BMI and WC. Estimation of sensitivity, specificity, positive and negative predictive values of NC by previous studies [59,64] suggest that NC performs better than WC in the assessment of metabolic health and NC is capable of predicting excess fat and cardiovascular risk factors. Blood pres-sure is one of the most important complications of obesity.…”
Section: Discussionmentioning
confidence: 95%